2016 IEEE 19th International Conference on Intelligent Transportation Systems (ITSC) 2016
DOI: 10.1109/itsc.2016.7795920
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility assessment to realise vehicle teleoperation using cellular networks

Abstract: Future cellular networks (5G) will be used for a diversity of use cases. Transportation is one domain where cellular networks can play a significant role not only in connecting autonomous vehicles to other vehicles, infrastructures, and people, but also in realizing vehicle teleoperation i.e., vehicle driven by an operator from a distance. In this paper, we assess the feasibility of using a cellular network to realise vehicle teleoperation. We identify the network requirements for a teleoperated vehicle use ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 8 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…In parallel, several field trials have shown the first benefits of C-V2X. For instance, in [31], the feasibility of teleoperated driving based on LTE networks is shown in a testbed. However, a more comprehensive analysis of drive test measurements shows that varying radio conditions and handovers could prevent achieving the required latency in certain spots and hours [32].…”
Section: Related Workmentioning
confidence: 99%
“…In parallel, several field trials have shown the first benefits of C-V2X. For instance, in [31], the feasibility of teleoperated driving based on LTE networks is shown in a testbed. However, a more comprehensive analysis of drive test measurements shows that varying radio conditions and handovers could prevent achieving the required latency in certain spots and hours [32].…”
Section: Related Workmentioning
confidence: 99%
“…In this manner, a vehicle may use a cellular connection for media consumption, freeing additional cellular or mesh networking technologies for use in safety-critical and time-sensitive applications. As 5G networking technologies roll out and costs fall, vehicles may indeed rely on direct cellular technologies to facilitate connectivity for critical applications [58]- [60]. Such technology offers high bandwidth (1Gb/s) for vehicles, and use of femtocells allows this connection to be repurposed by vehicle occupants' own devices [61].…”
Section: Intervehicle Networkmentioning
confidence: 99%
“…Eventually, 5G cellular will support high bandwidth, long range and low latency direct-tocloud connectivity, minimizing requisite vehicle density and improving the richness of data stored in vehicle mirrors [182]. Feasibility assessments show promise using this technology in the context of realtime vehicle teleoperation or for safety services today using V2V technology [60], [182], [183].…”
Section: A Communications Designmentioning
confidence: 99%
“…Dedicated short range communications and visible light communication are wireless communication technologies that are currently used presently but are not suitable for long distance communication. The 5G mobile network is best suited for vehicle teleoperation as it allows covering longer distances with a high throughput and low latency for continuous video streaming [36].…”
Section: Tele-operated Drivingmentioning
confidence: 99%